2006
DOI: 10.1002/anie.200502574
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Carbon–Carbon Bond Formation Reactions between TCNE or TCNQ and a Quinonoid Ring

Abstract: C‐substituted zwitterionic 6π+6π benzoquinonemonoimines are obtained by a CC bond formation reaction. A selective, formal insertion of tetracyanoethylene (TCNE) or 7,7′,8,8′‐tetracyanoquinodimethane (TCNQ) into a CH bond of a quinonoid ring provides a new, general synthetic method in quinonoid chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 72 publications
1
15
1
Order By: Relevance
“…In particular, benzoquinonemonoimines have been found to display unique properties in various areas such as color, [34] organic, [35,36] supramolecular, [37] coordination, and organometallic chemistry [37][38][39][40][41][42][43][44] and homogeneous catalysis. [39,43,45] The first member of a new family of 12π-electron quinone-based zwitterions (1, R = tBu) was reported in 2002.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, benzoquinonemonoimines have been found to display unique properties in various areas such as color, [34] organic, [35,36] supramolecular, [37] coordination, and organometallic chemistry [37][38][39][40][41][42][43][44] and homogeneous catalysis. [39,43,45] The first member of a new family of 12π-electron quinone-based zwitterions (1, R = tBu) was reported in 2002.…”
Section: Introductionmentioning
confidence: 99%
“…53 The critical layer thickness at the onset of island formation cannot be ascertained from our measurements here, but the very large substrate signal evident in the XPS data is indicative of the formation of a very thin (1-3 nm) molecular overlayer before island growth is initiated. The crystal packing of the TCNQ-derived p-benzoquinonemonoimine zwitterion 4, first described in prior work, [46][47][48] presents multiple opportunities for strong hydrogen bonding, as illustrated in Fig. 8.…”
Section: Resultsmentioning
confidence: 94%
“…1 2 as the C-substituent. [46][47][48] Graphene was grown on copper foil by Chemical Vapor Deposition (CVD) at 1000 uC, at the pressure of 1.4 Torr for 30 min using the gas mixture of C 2 H 2 (1.4 sccm) and H 2 (2 sccm). The zwitterions were deposited on clean gold and graphene substrates from a CH 2 Cl 2 solution, as noted in prior work.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Organic compounds containing a quinonoid fragment are of great interest because of their intrinsic properties and their numerous applications in chemistry, physical chemistry and biology. In particular, benzoquinonemonoimines have been found to display unique properties in various areas such as coloring, 27 organic, 28,29 supramolecular, 30 coordination, organometallic chemistry 30,31,38,39 and homogeneous catalysis. [32][33][34][35][36][37] Previous studies have shown that the reactions between alkylamines or arylamines and benzoquinone gave a trans-dialkylaminobenzoquinone or trans-diarylamino-benzoquinone and monoarylamino products.…”
Section: Introductionmentioning
confidence: 99%